UPAYA PENINGKATAN HASIL BELAJAR IPS DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD PADA SISWA KELAS VA SDN 004 BAGAN BESAR DUMAI - Paidi (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
The background of this research is the teacher-centered social studies learning process, where the teacher uses the lecture method. This leads to students being less motivated in the learning process, resulting in them being less vigorous and actively asking questions during the delivery of learning materials. Efforts to fix this problem involve conducting action research. This study aims to improve the skills of teachers and student activities to improve learning outcomes in Social Sciences (IPS) for students in class VA of SDN 004 VA Bagan Besar. Subjects were students of class VA SDN 004 Bagan Besar Dumai, totaling 25 students consisting of 11 male students and 14 female students. The data used in this study are the activities of teachers and students, and Social Sciences learning outcomes. The results of this study indicate that: (a) the activities of teachers obtain a score of 32 (61.54%) with enough categories. In the first cycle, the second meeting was given a score of 38 (73.01%) in both categories. In the second cycle, the first meeting obtained a score of 50 (96.15%) with a very good category, and the second cycle's second meeting obtained a score of 51 (98.08%) with a very good category. Besides, student activity also increased; in the first cycle, the first meeting obtained a score of 20 (62.5%) with enough categories, and the first cycle's second meeting obtained a score of 23 (68.75%) in both categories. In the second cycle, the first meeting obtained a score of 28 (87.5%) with a very good category, and the second cycle's second meeting obtained a score of 30 (93.75%) with a very good category; and (b) the results of students in each cycle have increased. On the basis of the results of social studies scores, students get a low category with an average value of 48.8. In the first cycle, a sufficient category was obtained with an average value of 56.92. And the second cycle obtained both categories with an average value of 73.84.